Cross sectional study of the ability to lay up children aged 6-11 years - Isti Dwi Puspita Wati; Fifukha Dwi Khory; Procorpio B Dafun (Multilateral : Jurnal Pendidikan Jasmani dan Olahraga, 2024)
This research is a cross-sectional study on the ability of elementary school children aged 6-11 years to throw in the basic lay-up technique. This research is a descriptive study, with the entire population being sampled, totaling 244 children, consisting of 38 children aged six years, 29 children aged seven years, 50 children aged eight years, 30 children aged nine years, 41 children aged ten years, and 56 children 11 years old. The instruments used are tests and measurements. The test chosen is the lay-up test; each child is tested for the ability to lay up on five occasions. Admission was scored 1, and non-entry was scored 0. Data were analyzed using Excel and SPSS and presented as measures of central tendency and graphs. The results showed that the child's ability has significantly increased from time to time in terms of age. As he gets older, his ability to lay up increases